The study about the factors influence corporate social responsibilities (CSR) performance at the Immigration Department of Terengganu / Nur Amirah Hizuddin - Hizuddin, Nur Amirah (2014)
This study was carried out to identify the factors influence Corporate Social Responsibilities (CSR) performance in an organization. In chapter one, the researcher discussed about the background of the study. This research studied about the activities in CSR as the independent variables toward the CSR performance in organization as the dependent variables. The objectives of this study were to identify the influence of Corporate Social Responsibilities performance in the organization, to identify either economic responsibility influence CSR performance in the organization, to identify either ethical responsibility influence CSR performance in the organization also to identify either philanthropy responsibility influence CSR performance in the organization. In chapter three, the methodology used for this research has been discussed. The methodology is the method used by the researcher in finding the result while completing this research. This is including research design, sampling frame, population, sampling technique, and sample size, unit of analysis, instrument, and validity of instrument, data collection procedures and methods of data analysis. The researcher used convenience sampling technique. The scope of study only revolved within the organization and chose workers from the certain department as respondent for the research. The researcher chose workers from the Immigration Department of Terengganu as a scope of the study.